ANALISIS TREN KERAGAMAN PENULIS DOMESTIK DAN INTERNASIONAL PADA PUBLIKASI JURNAL BAREKENG - Rahangmetan, Keizya; Pokar, Esteria; Lewaherilla, Norisca; Patty, Dyana; Lesnussa, Yopi Andry (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study was conducted as part of the Internship Program (PKL) of the Statistics Study Program, carried out in the administrative editorial management division of the BAREKENG Journal. The activities included collecting and processing publication data to support the evaluation of editorial performance and the mapping of the journal’s internationalization process. This research aims to analyze trends in the diversity of domestic and international authors in BAREKENG Journal publications during the 2007–2025 period. The data were obtained from the journal’s publication archives and processed through several stages, including author affiliation classification, grouping by publication period, and analyzing the development of domestic and international author proportions. The analysis was conducted using descriptive quantitative methods and presented in the form of trend graphs. The results show that the number of domestic authors increased significantly after 2020, reaching 864 authors in 2025. Contributions from international authors first appeared in 2021 and continued to grow, with the highest number recorded at 61 authors in 2025. These findings indicate that the BAREKENG Journal is not only growing at the national level but is also beginning to attract attention from the international academic community. This study is expected to provide an overview of the dynamics of author contributions and the journal’s position in the internationalization process, as well as serve as a basis for strengthening future journal management strategies.